Mason Grace's Magical Laces - Evans Willow (London; Hodder Children's Books, 2022)
Filled with magic, friendship and fun, this is a charming story about joining in and always trying your very best. Mason is a little worried about the Big Summer Sports Day. What if he trips and falls? What if he loses at everything? But Gran has just the thing to help him find the confidence to join in... magical laces! Before they can work their magic, Mason must learn to tie them himself. With the help of his favourite toy, Billy Bunny, he learns to tie his laces, and is soon ready to win some races!
Keywords: Picture books for children